SELF-REGULATED LEARNING MODEL WITH MIND MAP TO IMPROVE STUDENTS COGNITION AND METACOGNITION SKILLS IN SOLVING CHEMICAL PROBLEMS - Syahmani, Syahmani (JPPS (Jurnal Penelitian Pendidikan Sains), 2019)
The research has been conducted on the application of Self-Regulated Learning (SRL) model with mind map in solving chemical problem on Hydrolysis Salt material in class XI MIPA . This study aims to improve (1) implementation SRL model with mind map in classroom, (2) student activity, (3) learning outcomes of cognition, and (4) metacognition skills. The study used a classroom action research design consisting of two cycles with four learning meetings and two evaluation meetings. The subjects of this study were students of class XI MIPA 6 SMAN 7 Banjarmasin with 36 students. Instrument of research in the form of metacognition skill and cognition test instrument, observation sheet of teacher and student activity, and questionnaire of metacognition skill. Data were analyzed by using descriptive analysis of quantitative and qualitative. The results showed that there was an increase (1) teacher activity from good category to be very good, (2) student activity from active category become very active, (3) mastery of cognition learning result from 44,44% to 88,89%, and (4) metacognition skills of the category began to develop into a well-developed.